Implikasi Legalisme Otokratis Terhadap Penegakan Hukum Hak Individual Warga Negara (Studi Atas Putusan No. 55/G/2016/PTUN.MTR jo. Putusan No. 112/B/2017/PT.TUN.SBY jo. Putusan Mahkamah Agung No. 37/K/TUN/2018) - Imam Kadir; Yudha Agung Pratama (Journal Law and Government, 2025)
Along with the dynamics of governance that increasingly leads to a process of autocratization that tends to be counterproductive to the values of constitutionalism and seems to destroy the will of the wider community, which is shown through the practice of autocratic legalism by utilizing the power of the three branches of power to perpetuate a unilateral interest through legal reform so that it appears to be legal and constitutional but essentially deviates from the principles of the rule of law, Where one of its main characteristics is to provide protection for human rights, so this research is present to reveal the causal relationship between the practice of autocratic legalism and its impact on the enforcement of citizens' individual rights within the framework of analyzing several court decisions. The method used in the research is normative research using several approaches, namely the statute apporoach, conceptual approach, and case study approach. The results of the study concluded that: first, in several court decisions, judges in formulating their ratio decidendi did not seem to apply the law properly as a result of only relying on formal truth and negating material facts which in fact are the truth that must be prioritized so that the arbitrary actions of the government seemed to be “normalized” through court decisions. Second, from this situation, of course the implication of autocratic legalism on law enforcement of citizens' individual rights is the abuse of government power by power holders for one-sided interests by overriding the individual rights of citizens, including human rightsvaccines are more due to global supply issues and high demand than Australia's violation of Article 31 TRIPS. This research confirms the importance of compulsory licenses in the face of the global health crisis. A fair and effective implementation of compulsory licenses can improve access to essential medicines, support public health, and fulfill the principles of fairness in licensing.